From the first industrial revolution to industry 4.0: Changes in innovative work behaviours and effects on the global economies - Şenel Uzunkaya, Seçil (Springer, 2020)
In this study, the development of innovative business behaviour on a company basis has been examined over the years. The first industrial revolution started with the use of steam engines in England. The most important effect of this process on business behaviour is the transition to mass production. To meet the product demands of the growing population, a lot of production was needed in a short time. In addition to the mentioned issue, the second industrial revolution started in the United States. The most important issue in this revolution is the production with the help of electrical energy. This contributed to increasing the production volume. On the other hand, computer and internet concepts have an important role in the third industrial revolution. This has enabled the trade volume to increase. In addition, robot technology came to the fore in the fourth industrial revolution. In this process, many stages in the production process are performed by machines instead of manpower. As can be seen from above, technological developments play an important role in the formation of industrial revolutions. This situation has very important effects on the business behaviour of companies.
Keywords: Global Economies; Innovative Work Behaviours; Industry 4.0